(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
A constructivist learner should be able to construct their own knowledge. This study developed inductive reasoning worksheet to guide the students in constructing and understanding inorganic compound nomenclature. The developed worksheet was considered as feasible and was implemented to 36 senior high schools students in Palangka Raya, Central Kalimantan-Indonesia. The worksheet effectively guided the students to construct and understand inorganic compound nomenclature.The ability to construct inorganic compound nomenclature was positively correlated with the understanding of the nomenclature concept.